FEATURES OF INDEPENDENT WORK OF STUDENTS AT THE DEPARTMENT OF PROPADEUTICS OF CHILD DISEASES - Sh.M. Ibatova; Islamova S.S; Islamova D.S. (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
To improve the educational process in a medical university, much attention is paid to the organization of independent work of students (IWS). The article presents the purpose and objectives of independent work and reveals its role in the organization of the educational process. SRS is carried out on the basis of modern technologies and is an important element of the professional training of a future specialist. IWS is a type of activity carried out under the guidance, but without the direct participation of the teacher in a specially allotted educational or extracurricular time. This is a special form of learning according to the tasks of the teacher, the implementation of which requires active mental activity of the student. At the Department of Propaedeutics of Childhood Diseases, the teacher distributes the topics of independent work according to the calendar-thematic plan, taking into account his interests and individual capabilities. After receiving the topic, the student independently searches for material on a given topic in the library of the institute, gets acquainted with the necessary literature, finds the necessary information on the Internet and prepares a presentation. The teacher monitors the work of students who have prepared a report and controls the correctness of their assessments according to the assessment table developed at the department. Conducting independent work of students in this form shows the effectiveness of the knowledge gained, the high level of their theoretical and practical training, their personal qualities, contributes to the development of clinical thinking, attention, performance, and thus plays an important role in improving the educational process.